Actinomycotic Osteomyelitis of Maxilla Presenting as Oroantral Fistula: A Rare Case Report - Ashalata Gannepalli; Bhargavi Krishna Ayinampudi; Pacha Venkat Baghirath; G. Venkateshwara Reddy (Case Reports in Dentistry)
Actinomycosis is a chronic granulomatous infection caused by Actinomyces species which may involve only soft tissue or bone or the two together. Actinomycotic osteomyelitis of maxilla is relatively rare when compared to mandible. These are normal commensals and become pathogens when they gain entry into tissue layers and bone where they establish and maintain an anaerobic environment with extensive sclerosis and fibrosis. This infection spreads contiguously, frequently ignoring tissue planes and surrounding tissues or organ. The portal of entry may be pulpal, periodontal infection, and so forth which may lead to involvement of adjacent structures as pharynx, larynx, tonsils, and paranasal sinuses and has the propensity to damage extensively. Diagnosis is often delayed and is usually based on histopathology as they are cultured in fewer cases. The chronic clinical course without regional lymphadenopathy may be essential in diagnosis. The management of actinomycotic osteomyelitis is surgical debridement of necrotic tissue combined with antibiotics for 3–6 months. The primary actinomycosis arising within the maxilla with contiguous involvement of paranasal sinus with formation of oroantral fistula is rare. Hence, we present a 50-year-old female patient with chronic sclerosing osteomyelitis of maxilla which presented as oroantral fistula with suppurative and sclerotic features.